1998
DOI: 10.1136/fn.78.2.f121
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden and genetic defects of thrombophilia in childhood porencephaly

Abstract: Aims-To determine to what extent the Arg 506 to Gln point mutation in the factor V gene and further genetic factors of thrombophilia aVect the risk of porencephaly in neonates and infants. Methods-The Arg 506 to Gln mutation, factor V, protein C, protein S, antithrombin, antiphospholipid antibodies and lipoprotein (a) (Lp(a)) were retrospectively measured in neonates and children with porencephaly (n=24). Results-Genetic risk factors for thrombophilia were diagnosed in 16 of these 24 patients: heterozygous fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 34 publications
2
66
2
Order By: Relevance
“…23,38,39 The heterozygous FV G1691A genotype and protein C deficiency were found in another 6 cases. The heterozygous FV gene mutation has recently been suggested to be an important risk factor for childhood antenatal porencephaly 15 and is associated with a significant OR of 3.95 in neonatal stroke patients. The results reported from this subgroup analysis are in clear contrast to data published by Zenz et al 20 and McColl et al 22 This discrepancy is due mainly to the small number of investigated cases and the different study designs, and it underlines the need for larger subgroup analyses in childhood patients as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,38,39 The heterozygous FV G1691A genotype and protein C deficiency were found in another 6 cases. The heterozygous FV gene mutation has recently been suggested to be an important risk factor for childhood antenatal porencephaly 15 and is associated with a significant OR of 3.95 in neonatal stroke patients. The results reported from this subgroup analysis are in clear contrast to data published by Zenz et al 20 and McColl et al 22 This discrepancy is due mainly to the small number of investigated cases and the different study designs, and it underlines the need for larger subgroup analyses in childhood patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…Results of available studies differ, mainly because of differences in the study populations, age groups, or study designs. [15][16][17][18][19][20][21][22][23][24][25] Very recently, we have shown that an increased Lp(a) level, the FV G1691A mutation, the PT 20210A allele, and the homozygous C677T polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene are significant risk factors for spontaneous stroke in childhood. 23 That study, however, did not include neonatal and child patients with additional acquired risk factors.…”
mentioning
confidence: 99%
“…109,131,132 Congenital protein C deficiency, protein S deficiency, factor V Leiden mutation, and increased lipoprotein (a) have all been reported in newborns and children with perinatal infarction. 104,133,134 Acquired conditions are more frequent and include the presence of transplacentally derived maternal antiphospholipid antibodies (anticardiolipin antibodies, lupus anticoagulant) 135,136 and acquired deficiencies of protein C, protein S, AT, and activated protein C resistance.…”
Section: Complications Of Svtmentioning
confidence: 99%
“…Being a commonly performed genetic test with established population prevalence makes previous reports of much higher than expected rates seem significant. [29][30][31][32] As a constant genetic factor present from birth, FVL also avoids potentially complicating, confounding issues of neonatal versus childhood testing and developmental hemostasis. However, our results demonstrated rates of FVL (as well as prothrombin gene mutations) comparable to those in the general population.…”
Section: Discussionmentioning
confidence: 99%